The Students’ Needs in Learning Research Methodology in Linguistics - Sukma Septian Nasution; Tito Dimas Atmawijaya; Abdul Aziz (EDUVELOP, 2021)
This study aims at investigating the students’ needs analysis in learning Research in Linguistics at a university in Indonesia. Its main focus is on the students’ academic needs including difficulties of the materials, learning methods, styles and goals, level of understanding on linguistic research issues, course planning, instructional materials and practices, and evaluation. Using descriptive analytical method, a set of questionnaires was employed in Likert-scale formula. It encompassed samples of 105 learners of English Letter’s study program of the university. To validate the finding of the questionnaire, semi-structured interview to the lecturers and the students were also conducted. It results in that the leaners need; 1) the suitability of the materials composition for learners’ need; 2) using group discussion method in learning activity; 3) a step-by-step process to support practical experience in collecting and analyzing data; 4) Overtly relating components of an academic journal article to the elements of developing a research project. The study ends with a recommendation for composing course materials of Research in Linguistics suited with the afore-mentioned findings.